Implementation of Nanoscale Secondary‐Ion Mass Spectrometry Analyses: Application to Ni‐Based Superalloys. Issue 9 (20th December 2021) - Almoric, Jean; Durand, Malik; Seret, Anthony; Nicolaÿ, Alexis; Houel, Arnaud; Berbezier, Isabelle; Bozzolo, Nathalie
Abstract : Secondary‐ion mass spectrometry (SIMS) is probably the most widely used chemical analysis technique in semiconductor science and in metallurgy because of its ultimate sensitivity to all elements and in particular to light elements providing semiquantitative information on the depth distribution of elements, for instance, doping elements (i.e., B, H), contaminants (i.e., C and O), chemical gradients, and segregation in thin films and at interfaces, etc. With the size shrinking of systems, high‐resolution 3D chemical imaging is becoming a prerequisite for the development of new materials at the nanoscale and for the deep understanding of the correlation between their properties and functionalities. Herein, the development of an innovative analytical SIMS implemented in a focused ion beam (FIB) (using Ga source)/scanning electron microscope (SEM) is reported. The equipment enables to give elemental chemical mapping at very high resolution (<30 nm) by precise optimization of the secondary‐ion optics and detection, while preserving excellent sensitivity, thanks to the integration of a gas injection system (GIS), which improves a positive (negative) ionization rate with oxygen (cesium) injection. The capability of the technique is demonstrated with nanoscale characterization of Ni‐based superalloys with broad applications in the manufacturing of engine parts and accessories for aircraft and aerospace equipment. Abstract : Herein, the development of an innovative orthogonal time‐of‐flight secondary‐ion mass spectrometry implemented in focused ion beam (using a Ga source)/scanning electron microscope is reported. The capabilities of this instrument are demonstrated with the nanoscale characterization of Ni‐based superalloys at very high resolution (<30 nm) and high mass resolution (4500 on 28 Si).